Development of polysaccharide-coated layered double hydroxide nanocomposites for enhanced oral insulin delivery - Huiwen Pang; Youzhi Wu; Yang Chen; Chen Chen; Xuqiang Nie; Peng Li; Guojun Huang; Zhi Ping Xu; Felicity Y. Han (Drug Delivery and Translational Research, 2024)
Oral insulin (INS) is predicted to have the most therapeutic advantages in treating diabetes to repress hepatic glucose production through its potential to mimic the endogenous insulin pathway. Many oral insulin delivery systems have been investigated. Layered double hydroxide (LDH) as an inorganic material has been widely used in drug delivery thanks to its appealing features such as good biocompatibility, low toxicity, and excellent loading capability. However, when used in oral drug delivery, the effectiveness of LDH is limited due to the acidic degradation in the stomach. In this study, to overcome these challenges, chitosan (Chi) and alginate (Alg) dual-coated LDH nanocomposites with the loading of insulin (Alg-Chi-LDH@INS) were developed by the layered-by-layered method for oral insulin delivery with dynamic size of ~ 350.8 nm, negative charge of ~ − 13.0 mV, and dispersity index 0.228. The insulin release profile was evaluated by ultraviolet–visible spectroscopy. The drug release profiles evidenced that alginate and chitosan coating partially protect insulin release from a burst release in acidic conditions. The analysis using flow cytometry showed that chitosan coating significantly enhanced the uptake of LDH@INS by Caco-2 cells compared to unmodified LDH and free insulin. Further in the in vivo study in streptozocin-induced diabetic mice, a significant hypoglycemic effect was maintained following oral administration with great biocompatibility (~ 50% blood glucose level reduction at 4 h). This research has thus provided a potential nanocomposite system for oral delivery of insulin. Graphical Abstract

Protective effect of solanesol in glucose-induced hepatocyte injury: Mechanistic insights on oxidative stress and mitochondrial preservation - Yiqiu Liu; Musen Lin; Xingrui Mu; Lin Qin; Junyu Deng; Ye Liu; Xingqian Wu; Wenjie He; Huiwen Pang; Felicity Han; Chengxin Sun; Xuqiang Nie (Chemico-Biological Interactions, 2023)

Sustained-release ketamine-loaded lipid-particulate system: in vivo assessment in mice - Weizhi Xu; Faheem Maqbool; Vinod Kumar; James R. Falconer; Cedric S. Cui; Trent M. Woodruff; Karin Borges; Andrew K. Whittaker; Maree T. Smith; Felicity Y. Han (Drug Delivery and Translational Research, 2022)

Sustained release ketamine-loaded porous silicon-PLGA microparticles prepared by an optimized supercritical CO2 process - Weizhi Xu; Zonglan Zhao; James Falconer; Andrew K. Whittaker; Amirali Popat; Maree T. Smith; Tushar Kumeria; Felicity Y. Han (Drug Delivery and Translational Research, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Use of Microfluidics to Fabricate Bioerodable Lipid Hybrid Nanoparticles Containing Hydromorphone or Ketamine for the Relief of Intractable Pain - Minze Zhu; Andrew K. Whittaker; Xingyu Jiang; Rupei Tang; Xuanyu Li; Weizhi Xu; Changkui Fu; Maree T Smith; Felicity Y Han (Pharmaceutical Research, 2020)